The credibility of advertising vs publicity for new FMCGs in Turkey - Celebi, Serra (Emerald Group Publishing Ltd, 2007)
Purpose - The purpose of this study is to investigate the credibility of advertising vs publicity; to examine the credibility of advertising including a promotional endorser (APE) and publicity including a promotional endorser (PPE); to compare the credibility of advertising across the different demographic segments; and to explore the important factors affecting consumers' shopping considerations of new fast moving consumer goods (FMCGs) in Turkey. Design/methodology/approach - The data was gathered by a telephone survey from a sample of 717 of which 348 respondents wanted to participate from three of Turkey's largest cities, Istanbul, Ankara, and Izmir. The systematic sampling was exercised to select the sample. chi(2) and t-tests were computed and the results of them were significant at 0.05 level. Findings - For announcing new FMCGs in Turkey, advertising was found to be more credible by the participants with higher income. Respondents' shopping decisions of new FMCGs were affected by price and quality more than the other factors. Consumers tended to rely on publicity more than advertising; more than APE; and more than PPE. They also tended to count PPE more credible than APE. Originality/value - The findings suggest that it would be appropriate for advertising managers, who wish to market to Turkey, to consider recipients' income levels in regard to the credibility of advertising for new FMCGs. It is also important to note for international companies that price and quality play a major role on Turkish consumers' shopping decisions of new FMCGs among the other factors including experiments, organizational trust, and word-of-mouth.
Keywords: Advertising; Public relations; Fast moving consumer goods; Consumer behaviour; Turkey